HEALTH EDUCATION, TRAINING OF PUBLIC EXERCISE AND INFANT MASSAGE FOR cadres and the community in BEUNOT VILLAGE, SYAMTALIRA DISTRICT, BAYU UTARA - Fitri Hijri Khana; Rika Mursyida (Universitas Mercu Buana, 2022)
The postpartum period is the post-partum recovery period until all of the female reproductive organs have recovered. This puerperal period lasts about 6-8 weeks after delivery. Things that need to be considered during the puerperium include temperature, lochia expenditure, breasts, urinary tract, and cardiovascular system. This exercise is carried out from the first day after giving birth to the tenth day and serves to restore health conditions, accelerate healing, prevent complications, restore and improve muscle tension after pregnancy, especially in the muscles of the back, pelvic floor, and abdomen. Baby massage is important to help baby develop optimally. This Community Service consists of 3 activities, namely health education and training for postpartum gymnastics and baby massage. The health education methods used were lectures and questions and answers, training for postpartum gymnastics and baby massage on proper postpartum gymnastics and baby massage techniques and practicing them directly. The purpose of this Community Service is to restore body fitness after childbirth, while baby massage is for optimal baby growth and development. The participants of health education for postpartum gymnastics and baby massage were 20 people. Community service activities are carried out for 1 month from 07 February to 05 March 2022 in Beunot Village, Syamtalira Bayu District. After participating in this activity, the participants understood and were able to practice postpartum gymnastics and Baby Massage independently.